Model Pendidikan Tradisionalisme Dalam Kegiatan Pembelajaran di Madrasah Diniyah: Tinjauan Filsafat Pendidikan Islam - Abul Mafaakhir; Moh. Sugeng Solehuddin (https://ejournal.insuriponorogo.ac.id/, 2023)
Islamic education at Madrasah Diniyah plays an important role in shaping the Islamic character and identity of the next generation of Muslims. This article presents an overview of the traditionalist education model applied in learning activities at Madrasah Diniyah, with a special focus on the perspective of Islamic educational philosophy. Through a qualitative approach, this research explores the values, characteristics of Islamic madrasas and traditionalism in organizing learning. In the context of Islamic educational philosophy, this article explores the fundamental principles that form the philosophical basis of the traditionalist educational model at Madrasah Diniyah. Through document analysis, interviews and classroom observations, this research tries to explain the relationship between the teachings of the Al-Qur’an and Sunnah and the practice of learning at Madrasah Diniyah. The research results highlight the positive contribution of the traditionalist education model to the formation of students' Islamic and moral character. It was found that teaching methods that emphasize memorizing sacred Islamic texts, developing noble morals, and instilling Islamic heritage values ​​are important points in this model. The discussion in the article discusses the challenges faced by the traditionalist education model, including adaptation to modern-day demands and the integration of technology in the learning process. This research provides a deeper understanding of how the traditionalism model at Madrasah Diniyah can remain relevant and contribute positively in the context of Islamic education in the contemporary era. The conclusion underlines the importance of understanding philosophical values ​​and absorbing the essence of the traditionalist educational model as an integral part of inheriting Islamic wisdom.